2002
DOI: 10.3348/kjr.2002.3.3.171
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion MR Imaging: Clinical Utility for the Differential Diagnosis of Various Brain Tumors

Abstract: ObjectiveTo determine the utility of perfusion MR imaging in the differential diagnosis of brain tumors.Materials and MethodsFifty-seven patients with pathologically proven brain tumors (21 high-grade gliomas, 8 low-grade gliomas, 8 lymphomas, 6 hemangioblastomas, 7 metastases, and 7 various other tumors) were included in this study. Relative cerebral blood volume (rCBV) and time-to-peak (TTP) ratios were quantitatively analyzed and the rCBV grade of each tumor was also visually assessed on an rCBV map.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 22 publications
4
36
0
1
Order By: Relevance
“…Metastatic tumors spread into the CNS via hematogenous routes and induce neovascularization as they grow and expand. Several studies in the literature reported that rCBV ratios are not useful for discrimination (20,23). In our study we also demonstrated that the rCBV ratios of 25 patients with metastasis were not helpful for discriminating these tumors from high-grade gliomas.…”
Section: Metastasismentioning
confidence: 99%
See 2 more Smart Citations
“…Metastatic tumors spread into the CNS via hematogenous routes and induce neovascularization as they grow and expand. Several studies in the literature reported that rCBV ratios are not useful for discrimination (20,23). In our study we also demonstrated that the rCBV ratios of 25 patients with metastasis were not helpful for discriminating these tumors from high-grade gliomas.…”
Section: Metastasismentioning
confidence: 99%
“…In our study the nidus was hypervascular in all cases with PWI. Cho et al (20) demonstrated that increased rCBV ratios are helpful for differentiating pilocytic astrocytomas from hemangioblastomas, which is not possible with conventional images. In our study we also demonstrated that rCBV ratios were clearly increased and there was a statistically significant difference from all other intracranial masses.…”
Section: Hemangioblastomamentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphomas were found to be associated with lower rCBV values (5,9,10). The rCBV values of lymphoma are noted to be much less compared to high-grade gliomas (11,12). Few earlier studies highlighted salient features of enhancing malignant lesions based on rCBV measurements on DSC perfusion and with diffusion (DWI-ADC), but were not always confirmatory (9,13).…”
Section: Introductionmentioning
confidence: 99%
“…However, advanced MRI techniques like proton MR spectroscopy and perfusion helps in differentiating between them [1,2]. However, other approach to study and characterise various intracranial mass lesions would be to study their energy status and metabolic profile.…”
Section: Introductionmentioning
confidence: 99%